Contributions by D. Tsogt for study of Mongolia-China literature relations - U, Sarantsetseg (Mongolian Language and Literature Studies, 2024)
In this article, one of the main research topics in the study of Mongolian-Chinese literary communication is the folk tales and fiddle tales. For the first time, academicians B. Renchin and D. Tserensodnom studied them in Mongolia and published specific scientific information. Furthermore, Chinese scholars Dulaan and Tsogt have created detailed analytical works on specific genres and texts, paving the way for a new path in this direction. It is emphasized that the scholar who made a significant contribution to this direction with his works “Study of Fiddle Tales” and “Study of “Bodhi Khan the Wise” by the Luvsan Fiddler” is B. Tsogt, a professor at the Central University for Nationalities in Beijing, China. Монгол-хятад уран зохиолын харилцаа холбооны судлалд эрдэмтэн Д.Цогтын оруулсан хувь нэмэр Түлхүүр үг. Бэнсний үлгэр, хуурын үлгэр, Лувсан хуурч, Б.Цогт